Amazing Eggs - Hodgkins, Fran; Smith, Wendy 1955- (Novato, CA : Treasure Bay, 2011)
Learn about how some animals begin their lives by hatching out of an egg.
"Take turns reading!"--Cover.
100119
Keywords: Eggs -- Juvenile Litrature; Readers (Elementary)